Fabrication and Super-Antibacterial Property of Nanosilver/Sericin/Poly(ethylene oxide) Nanofibers through Electrospinning-Combined Postdeposition Method. (15th November 2016) - Li, Jia; Wang, Bo-Xiang; Cui, Yi-Fan; Yu, Zhi-Cai; Hao, Xu; Huang, Feng-Yuan; Cheng, De-Hong; Lu, Yan-Hua
Abstract : Nanosilver particle has been used in the nanofiber mats by mixing the nanosilver with the spinning solution for improving the antibacterial property. Although studies have shown that the antibacterial property of nanofiber mats gets increasing, the higher silver content and the larger released resistance of nanosilver from nanofiber mats are obvious. Here, the electrospinning-combined postdeposition method was used to prepare the nanosilver/sericin/poly(ethylene oxide) (Ag/SS/PEO) nanofiber mats and the bacterial reduction rates against Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) were analyzed. We found that the Ag/SS/PEO nanofiber mats were excellent antibacterial properties at the lower silver content and the bacterial reduction rates against S. aureus and E. coli all reached above 99.99%. Our data suggests that the antibacterial property can be improved by introducing the electrospinning-combined postdeposition method.